A method for preparing a high strength and toughness hard metal with a biomimetic laminated structure and a cutting tool
Patent Information
- Application Number
- CN202511899158.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-16
AI Technical Summary
[0012]为解决现有技术中存在的传统均质硬质合金的强韧倒置、高温失效、工艺低效,以及深冷-时效协同工艺存在的服役期微观裂纹、常规电阻时效温控精度差和析出相尺寸波动大的问题,本发明提供了一种仿生叠层结构高强韧硬质合金制备方法和切削刀具
[0038] 1. Biomimetic layered structures can effectively improve impact toughness by absorbing energy through crack deflection and interlayer slip.
Smart Images

Figure CN121571659B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cemented carbide materials technology, and in particular to a biomimetic layered high-strength and high-toughness cemented carbide, its preparation method, and cutting tools. Background Technology
[0002] As a core cutting material in high-end equipment manufacturing, the synergistic improvement of strength and toughness in cemented carbide has always been a bottleneck in the industry. Traditional homogeneous cemented carbide (such as the WC-Co system) is limited by a single binder phase, resulting in a triple contradiction:
[0003] 1. Inversion of strength and toughness: Although adding grain inhibitors such as VC / Cr3C2 can increase hardness (HV>2200), it causes the fracture toughness to drop sharply to 8-10 MPa·m¹ / ².
[0004] 2. High-temperature failure: The Co-based binder phase softens severely above 800℃ (Vickers hardness decay rate > 40%), and interface oxidation induces cracks;
[0005] 3. Inefficient process: Multi-stage aging treatment requires 3-5 hours and energy consumption is as high as 12kWh / kg.
[0006] To overcome the above limitations, existing technologies attempt two types of solutions:
[0007] Layered structure design: For example, a WC / TiC gradient transition layer is used, but due to physical mixing, brittle W-TiC phases are included between the layers, and the interlayer shear strength is only 283 MPa;
[0008] Nano-reinforcement: such as introducing graphene-CNT hybrids, but mechanical mixing causes CNT agglomeration, resulting in an impact toughness of less than 28 J / m².
[0009] In particular, the cryogenic-aging synergistic process has a fatal flaw:
[0010] Direct aging after cryogenic liquid nitrogen resulted in insufficient residual stress release (EBSD showed dislocation density > 10¹). 5 m⁻²), which can induce micro-cracks during service life;
[0011] Conventional resistors have poor temperature control accuracy during aging (±20℃), and the size fluctuation of precipitated phases is >30%. Summary of the Invention
[0012] To address the problems of inverted strength and toughness, high-temperature failure, and inefficient processing of traditional homogeneous cemented carbide, as well as the issues of microcracks during service life, poor temperature control accuracy, and large fluctuations in precipitated phase size in cryogenic-aging synergistic processes, this invention provides a biomimetic layered high-strength and high-toughness cemented carbide preparation method and cutting tool.
[0013] The technical solution adopted in this invention is:
[0014] A method for preparing a high-strength and high-toughness cemented carbide with a biomimetic layered structure as described above includes the following steps:
[0015] S1. Biomimetic stacked prefabrication: 65-70 parts of WC powder, 0.3-0.5 parts of Y2O3 powder, 0.05-0.1 parts of plasma-modified CNT-BN hybrid and 1.5-2.5 parts of BN nanosheets are mixed to prepare WC / BN slurry;
[0016] A TiC / BN slurry was prepared by mixing 9–10 parts of TiC powder with 3.5–5.5 parts of BN nanosheets.
[0017] WC / BN monolayer tapes and TiC / BN monolayer tapes were respectively produced by tape casting, and then cold isostatically pressed after being stacked alternately.
[0018] S2. Lattice distortion pretreatment: Immerse the billet in liquid nitrogen for 2-3 hours, then heat to room temperature;
[0019] S3. Magnetic field-assisted sintering: 12-15 parts of FeCrAlY alloy powder are filled into the interlayer voids of the billet;
[0020] Under a vertical magnetic field of 1–1.2T, the temperature is increased to 1450–1480℃ at a rate of 10–12℃ / min, and then hot-pressed and sintered at 48–50MPa for 1–2 hours.
[0021] S4. Post-stress relief treatment: cryogenically cool to -85 to -80℃ and hold for 1 to 2 hours, followed by pulsed current aging.
[0022] Preferably, in step S1, the plasma-modified CNT-BN hybrid is prepared by the following steps:
[0023] Multi-walled CNTs (Carbon Nanotubes) and hexagonal BN nanosheets were placed in a plasma reaction chamber and an Ar / N2 mixed gas was introduced. The volume ratio of Ar to N2 was 4:1 to 4.5:1. The mixture was treated for 30 to 40 minutes at a radio frequency power of 500 to 550 W and a gas pressure of 8 to 10 Pa, so that the BN nanosheets grew in situ on the CNT surface.
[0024] Preferably, in step S1, the preparation of WC / BN slurry includes:
[0025] Mix 25-30 parts of organic carrier with 0.4-0.6 parts of dispersant and stir until homogeneous to obtain liquid matrix one;
[0026] Add 65-70 parts of WC powder, 0.3-0.5 parts of Y2O3 powder, 0.05-0.1 parts of plasma-modified CNT-BN hybrid and 1.5-2.5 parts of BN nanosheets to the liquid matrix and mix evenly.
[0027] The preparation of TiC / BN slurry includes:
[0028] Mix 15-18 parts of organic carrier with 0.1-0.2 parts of dispersant and stir until homogeneous to obtain liquid matrix II;
[0029] Add 9-10 parts of TiC powder and 3.5-5.5 parts of BN nanosheets to the liquid matrix II and mix thoroughly.
[0030] The organic carrier is a 6-8 wt% polyvinyl butyral / ethanol solution, and the dispersant is herring oil.
[0031] Preferably, in step S1, WC / BN monolayer strips and TiC / BN monolayer strips are stacked alternately with a thickness ratio of 1:0.2 to 1:0.5 (which refers to the thickness ratio range of a single "WC layer + TiC layer" in a multilayer stacked structure).
[0032] Preferably, in step S3, the FeCrAlY alloy composition is Fe 70-73wt%, Cr 18-22wt%, Al 5-8wt%, and Y 0.5-1wt%.
[0033] Preferably, in step S3, the temperature is increased at a rate of 0.5°C / min in the range of 1000-1200°C during the hot pressing sintering process.
[0034] Preferably, in step S4, the cryogenic treatment employs liquid nitrogen injection at a rate of 5–5.5 L / min, with a surface temperature gradient of ≤50 °C / cm.
[0035] Preferably, in step S4, the pulse current aging parameters are a peak temperature of 600–620°C, a frequency of 50–55 Hz, and a cumulative time of 30–40 min.
[0036] A cutting tool, wherein the tip is made of an alloy prepared by the above-described method for preparing a high-strength and high-toughness cemented carbide with a biomimetic layered structure, wherein the biomimetic layering direction of the tip forms a 45° angle with the cutting force direction.
[0037] The beneficial effects of this invention are:
[0038] 1. Biomimetic layered structures can effectively improve impact toughness by absorbing energy through crack deflection and interlayer slip.
[0039] 2. Plasma-modified CNT-BN hybrids are used to avoid metal catalyst contamination, and BN nanosheets can also improve interlayer shear strength;
[0040] 3. FeCrAlY is used to form an Al2O3 / Y2O3 composite oxide film at high temperature to improve the oxidation resistance temperature;
[0041] 4. Inhibiting interlayer delamination through the directional alignment of BN nanosheets;
[0042] 5. Residual stress is eliminated by using a two-stage cryogenic combined magnetic field sintering process;
[0043] 6. A liquid matrix was prepared using a polyvinyl butyral / ethanol solution as an organic carrier and herring oil as a dispersant. The lamination interface bubbles were avoided and the porosity was reduced by casting.
[0044] 7. By promoting interdiffusion of interfacial elements between FeCrAlY alloy and WC through ultra-slow heating in the range of 1000-1200℃, the interfacial thickness is increased.
[0045] 8. Use liquid nitrogen jet cryogenic treatment to avoid macroscopic cracks caused by thermal stress concentration and reduce scrap rate;
[0046] 9. The uniform precipitation of nanoscale η phase (Co6W6C) is promoted by pulsed current aging, thus narrowing the hardness fluctuation range. Attached Figure Description
[0047] Figure 1 This is a schematic flowchart of the preparation method in an embodiment of the present invention. Detailed Implementation
[0048] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0049] Example 1
[0050] A method for preparing a biomimetic layered high-strength and high-toughness cemented carbide includes the following steps:
[0051] S1. Biomimetic laminated prefabrication: Mix 25 parts of organic carrier with 0.4 parts of dispersant and stir evenly to obtain liquid phase matrix one;
[0052] 65 parts of WC powder, 0.3 parts of Y2O3 powder, 0.05 parts of plasma-modified CNT-BN hybrid and 1.5 parts of BN nanosheets were added to liquid matrix one and mixed evenly to prepare WC / BN slurry;
[0053] The plasma-modified CNT-BN hybrid is prepared by the following steps:
[0054] Multi-walled CNTs and hexagonal BN nanosheets were placed in a plasma reaction chamber and an Ar / N2 mixed gas was introduced. The volume ratio of Ar to N2 was 4:1. The mixture was treated for 30 minutes at a radio frequency power of 500W and a gas pressure of 8Pa to allow BN nanosheets to grow in situ on the CNT surface.
[0055] 15 parts of organic carrier and 0.1 parts of dispersant were mixed and stirred evenly to obtain liquid phase matrix II;
[0056] Nine parts of TiC powder and 3.5 parts of BN nanosheets were added to liquid matrix II and mixed evenly to prepare TiC / BN slurry;
[0057] The organic carrier is a 6wt% polyvinyl butyral / ethanol solution, and the dispersant is herring oil.
[0058] WC / BN slurry and TiC / BN slurry were respectively made into WC / BN monolayer tapes and TiC / BN monolayer tapes by casting. The WC / BN monolayer tapes and TiC / BN monolayer tapes were stacked alternately with a thickness ratio of 1:0.2 and then cold isostatically pressed.
[0059] S2. Lattice distortion pretreatment: The billet is immersed in liquid nitrogen for 2 hours and then heated to room temperature;
[0060] S3, Magnetic field-assisted sintering: 12 parts of FeCrAlY alloy powder were filled into the interlayer voids of the billet;
[0061] Under a vertical magnetic field of 1T, the temperature is increased to 1450℃ at a rate of 10℃ / min, and hot-pressed and sintered at a pressure of 50MPa for 1 hour. During the hot-pressing and sintering process, the temperature is increased at a rate of 0.5℃ / min in the range of 1000 to 1200℃.
[0062] The FeCrAlY alloy composition is 70wt% Fe, 22wt% Cr, 7wt% Al, and 1wt% Y.
[0063] S4. Post-stress relief treatment: cryogenically cool to -85℃ and hold for 1 hour, followed by pulsed current aging. The cryogenic treatment uses liquid nitrogen spraying at a rate of 5L / min, with a surface temperature gradient of ≤50℃ / cm. The pulsed current aging parameters are a peak temperature of 600℃, a frequency of 50Hz, and a cumulative time of 30min.
[0064] Example 2
[0065] A method for preparing a biomimetic layered high-strength and high-toughness cemented carbide includes the following steps:
[0066] S1. Biomimetic laminated prefabrication: Mix 28 parts of organic carrier with 0.5 parts of dispersant and stir evenly to obtain liquid phase matrix one;
[0067] 68 parts of WC powder, 0.4 parts of Y2O3 powder, 0.08 parts of plasma-modified CNT-BN hybrid and 2 parts of BN nanosheets were added to liquid matrix 1 and mixed evenly to prepare WC / BN slurry;
[0068] The plasma-modified CNT-BN hybrid is prepared by the following steps:
[0069] Multi-walled CNTs and hexagonal BN nanosheets were placed in a plasma reaction chamber and an Ar / N2 mixed gas was introduced. The volume ratio of Ar to N2 was 4.3:1. The mixture was treated for 35 minutes at a radio frequency power of 530 W and a gas pressure of 9 Pa, so that the BN nanosheets grew in situ on the CNT surface.
[0070] 17 parts of organic carrier and 0.15 parts of dispersant were mixed and stirred evenly to obtain liquid phase matrix II;
[0071] 9.5 parts of TiC powder and 4.5 parts of BN nanosheets were added to liquid matrix II and mixed evenly to prepare TiC / BN slurry;
[0072] The organic carrier is a 7wt% polyvinyl butyral / ethanol solution, and the dispersant is herring oil.
[0073] WC / BN slurry and TiC / BN slurry were respectively made into WC / BN monolayer tapes and TiC / BN monolayer tapes by casting. The WC / BN monolayer tapes and TiC / BN monolayer tapes were stacked alternately with a thickness ratio of 1:0.4 and then cold isostatically pressed.
[0074] S2, Lattice distortion pretreatment: The billet is immersed in liquid nitrogen for 2.5 hours and then heated to room temperature;
[0075] S3. Magnetic field-assisted sintering: 14 parts of FeCrAlY alloy powder were filled into the interlayer voids of the billet.
[0076] Under a vertical magnetic field of 1.1T, the temperature was increased to 1465℃ at 11℃ / min, and hot-pressed and sintered at a pressure of 50MPa for 1.5h. During the hot-pressing and sintering process, the temperature was increased at a rate of 0.5℃ / min in the range of 1000~1200℃.
[0077] The FeCrAlY alloy composition is Fe 71.2wt%, Cr 20wt%, Al 8wt%, and Y 0.8wt%.
[0078] S4. Post-stress relief treatment: cryogenic to -83℃ and hold for 1.5h, followed by pulsed current aging. The cryogenic treatment uses liquid nitrogen spraying at a rate of 5.3L / min, with a surface temperature gradient of ≤50℃ / cm. The pulsed current aging parameters are a peak temperature of 610℃, a frequency of 53Hz, and a cumulative time of 35min.
[0079] Example 3
[0080] A method for preparing a biomimetic layered high-strength and high-toughness cemented carbide includes the following steps:
[0081] S1. Biomimetic laminated prefabrication: Mix 30 parts of organic carrier with 0.6 parts of dispersant and stir evenly to obtain liquid phase matrix one;
[0082] 70 parts WC powder, 0.5 parts Y2O3 powder, 0.1 parts plasma-modified CNT-BN hybrid and 2.5 parts BN nanosheets were added to liquid matrix one and mixed evenly to prepare WC / BN slurry;
[0083] The plasma-modified CNT-BN hybrid is prepared by the following steps:
[0084] Multi-walled CNTs and hexagonal BN nanosheets were placed in a plasma reaction chamber and an Ar / N2 mixed gas was introduced. The volume ratio of Ar to N2 was 4.5:1. The mixture was treated for 40 min at a radio frequency power of 550 W and a gas pressure of 10 Pa to allow BN nanosheets to grow in situ on the CNT surface.
[0085] 18 parts of organic carrier and 0.2 parts of dispersant were mixed and stirred evenly to obtain liquid phase matrix II;
[0086] 10 parts of TiC powder and 5.5 parts of BN nanosheets were added to liquid matrix II and mixed evenly to prepare TiC / BN slurry;
[0087] The organic carrier is an 8wt% polyvinyl butyral / ethanol solution, and the dispersant is herring oil.
[0088] WC / BN slurry and TiC / BN slurry were respectively made into WC / BN monolayer tapes and TiC / BN monolayer tapes by casting. The WC / BN monolayer tapes and TiC / BN monolayer tapes were stacked alternately with a thickness ratio of 1:0.2 and then cold isostatically pressed.
[0089] S2. Lattice distortion pretreatment: The billet is immersed in liquid nitrogen for 3 hours and then heated to room temperature;
[0090] S3. Magnetic field-assisted sintering: 15 parts of FeCrAlY alloy powder are filled into the interlayer voids of the billet;
[0091] Under a vertical magnetic field of 1.2T, the temperature was increased to 1480℃ at a rate of 12℃ / min, and then hot-pressed and sintered at a pressure of 50MPa for 2 hours. During the hot-pressing and sintering process, the temperature was increased at a rate of 0.5℃ / min in the range of 1000 to 1200℃.
[0092] S4. Post-stress relief treatment: cryogenic to -80℃ and hold for 2 hours, followed by pulsed current aging. The cryogenic treatment uses liquid nitrogen spraying at a rate of 5.5 L / min, with a surface temperature gradient of ≤50℃ / cm. The pulsed current aging parameters are a peak temperature of 620℃, a frequency of 55 Hz, and a cumulative time of 40 min.
[0093] In the above embodiments, a biomimetic stacked structure is formed by alternating stacking of WC and TiC layers. The TiC layer acts as a toughness buffer layer, causing cracks to deflect at the interlayer interface and improving impact toughness. In addition, the BN nanosheets are oriented perpendicular to the stacking direction, thereby improving the interlayer strength.
[0094] In the preparation of plasma-modified CNT-BN hybrids, active N* promotes the epitaxial growth of BN on the CNT surface to form a three-dimensional pinning network, which inhibits WC grain coarsening. The reduction in grain size is beneficial to improving yield strength, and the absence of Ni catalyst oxidation reduces the high-temperature hardness decay rate.
[0095] To address the problem of severe softening of traditional Co-based binders above 800℃, the above embodiments completely replace Co-Ni with FeCrAlY alloy, significantly improving its high-temperature oxidation resistance. At high temperatures, it selectively oxidizes to form a dense α-Al₂O₃ film (oxygen diffusion coefficient of only 10⁻¹). 4 (cm² / s), blocking oxygen diffusion inward:
[0096]
[0097] Y2O3 works synergistically with Al2O3, with Y³⁺ filling the Al2O3 grain boundaries, reducing the oxide film growth rate and significantly reducing oxidation weight gain.
[0098] By applying a vertical magnetic field during the pressing stage, the normals of the BN nanosheets are made parallel to the magnetic field, achieving directional alignment. This reduces thermal stress by utilizing their slip properties.
[0099] Residual stress is eliminated by a two-stage cryogenic combined with magnetic field sintering process. The parameters are controlled by liquid nitrogen jet cryogenic treatment, with a jetting rate of 5-5.5 L / min and a surface temperature gradient of ≤50℃ / cm. This reduces the thermal stress concentration factor, activates the dislocation slip system, reduces residual stress, avoids macroscopic cracks caused by thermal stress concentration, and reduces the scrap rate.
[0100] Polyvinyl butyral / ethanol solution was used as an organic carrier, and the concentration was controlled to form a continuous bonding network, which improved the tensile strength of the film. Meanwhile, the polar ends of the phospholipids in herring oil adsorbed BN nanosheets to improve viscosity stability. Casting was used to avoid bubbles at the interlayer interface and reduce porosity.
[0101] BN nanosheets exhibit significant magnetic anisotropy, with a magnetic susceptibility perpendicular to the c-axis (i.e., the direction normal to the basal plane). ) is much greater than the magnetic susceptibility parallel to the c-axis direction ( When a vertical DC magnetic field of 1T is applied to the green sheet after casting, the BN nanosheets will rotate under the influence of torque, causing their c-axis to be parallel to the direction of the magnetic field. Since the c-axis of the BN nanosheets is perpendicular to their two-dimensional sheet planes, this means that the sheet planes will eventually align perpendicular to the direction of the magnetic field, thus achieving an oriented arrangement perpendicular to the stacking direction in the stacked structure.
[0102] The physical principle of this process can be understood from the perspective of minimizing the magnetic energy of the system. The magnetic energy of BN nanosheets in a magnetic field. It can be represented as:
[0103]
[0104] in, It is the vacuum permeability. It is the volume of the BN nanosheets. It is magnetic susceptibility anisotropy. It is the magnetic field strength vector. It is the unit vector along the c-axis of the BN nanosheets. When the c-axis is parallel to the direction of the magnetic field, the magnetic energy of the system is at its lowest and the state is most stable. The magnetic field treatment stage before sintering provides the driving force for the BN nanosheets to overcome the viscous resistance of the slurry and rotate and align.
[0105] In the slurry preparation stage, the pre-mixing of the organic carrier (polyvinyl butyral / ethanol solution) and dispersant (herring oil) is crucial. The dispersant effectively reduces the interfacial energy between the BN nanosheets and the solvent, lowering the contact angle to approximately 15°, significantly improving the wettability of BN and reducing agglomeration caused by van der Waals forces. The low-viscosity slurry (viscosity controlled at 3000±200 mPa·s) provides the necessary flowability for the free rotation of the BN wafers in the subsequent magnetic field.
[0106] During tape casting, the shear force generated by the doctor blade initially induces the BN sheets to align parallel to the substrate direction. However, the immediately applied perpendicular magnetic field provides a stronger orientation driving energy, offsetting the effect of the shear force and ultimately locking the c-axis of the BN nanosheets firmly in the direction of the magnetic field. X-ray diffraction analysis of the crystal planes of the sintered sample revealed a full width at half maximum (FWHM) of less than 5°, and calculations showed that the orientation degree of BN was higher than 95%, demonstrating the high efficiency of this method.
[0107] This oriented arrangement structure brings two major performance advantages:
[0108] Excellent interlaminar stress dissipation: When thermal stress is generated along the stacking direction due to thermal cycling during service, vertically aligned BN can effectively dissipate stress by inducing interlaminar slip due to the extremely low shear modulus between its base surfaces. Finite element simulations show that, compared to random alignment, oriented alignment can reduce interlaminar thermal stress by more than 35%.
[0109] Highly efficient oxygen diffusion barrier: The BN sheets are arranged perpendicular to the stacking direction, which means that the diffusion path of oxygen perpendicular to the stacking direction (i.e., the thickness direction) is greatly lengthened and tortuous, like navigating a maze. This significantly slows down the rate of oxygen ion diffusion inward, resulting in a much lower oxidation weight gain of the material at high temperatures compared to traditional structures.
[0110] During hot pressing sintering, the ultra-slow heating rate in the range of 1000-1200℃ promotes the interdiffusion of interfacial elements between FeCrAlY alloy and WC, increases the Cr diffusion distance, increases the interface thickness, and improves the interfacial bonding energy.
[0111] By aging with pulsed current, a Joule heating effect is generated, which reduces the atomic diffusion activation energy and shortens the uniformity time of the nanoscale η phase (Co6W6C), avoiding the risk of grain boundary oxidation in traditional aging and resulting in more uniform precipitation. Electron wind can drive the directional migration of W atoms, reducing the size of the precipitated phase.
[0112] In summary, this invention, through three technological innovations—innovation of FeCrAlY binder phase composition, biomimetic layered structure design, and oxygen-free pulse aging process—has greatly solved the problems of high-temperature softening and interface oxidation failure of cemented carbide.
[0113] The cutting tip of a tool made from the aforementioned biomimetic layered high-strength and high-toughness cemented carbide can decompose the main cutting force into interlayer shear components, greatly reducing the stress concentration factor at the cutting edge and significantly improving the tool's service life.
[0114] Cutting tools made of cemented carbide produced using the methods of Examples 1-3 were compared with three commercially available conventional cemented carbide tools in cutting experiments. The cutting material was TC4 titanium alloy (aerospace grade, hardness HRC 36). The cutting parameters were a spindle speed of 120 m / min, a feed rate of 0.2 mm / rev, and a depth of cut of 2 mm. The cemented carbide tools produced using the methods of Examples 1-3 corresponded to the improved groups 1-3, while the purchased cemented carbide tools corresponded to the conventional groups 1-3. The experimental data comparison is shown in the table below:
[0115]
[0116] As can be seen, this invention combines innovative FeCrAlY binder phase composition, biomimetic layered structure design, and oxygen-free pulsed aging process. The high-temperature oxide film (Al2O3) inhibits the softening of the binder phase, the layered structure disperses the cutting force, and the nano-η phase enhances wear resistance, greatly improving tool life. Furthermore, the BN nanosheets optimize the heat conduction path, reduce the cutting temperature, inhibit oxidation, and reduce the surface roughness of the tool. This invention addresses industry pain points from three dimensions: materials, structure, and process, and has the technical advantage of replacing traditional tools.
[0117] The embodiments described above are merely illustrative of specific implementations of the present invention, and while the descriptions are detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing the biomimetic layered high-strength and high-toughness cemented carbide, characterized in that, Includes the following steps: S1. Biomimetic stacked prefabrication: 65-70 parts of WC powder, 0.3-0.5 parts of Y2O3 powder, 0.05-0.1 parts of plasma-modified CNT-BN hybrid and 1.5-2.5 parts of BN nanosheets are mixed to prepare WC / BN slurry; A TiC / BN slurry was prepared by mixing 9–10 parts of TiC powder with 3.5–5.5 parts of BN nanosheets. WC / BN monolayer strips and TiC / BN monolayer strips were respectively produced by tape casting. The WC / BN monolayer strips and TiC / BN monolayer strips were stacked alternately with a thickness ratio of 1:0.2 to 1:0.5 and then cold isostatically pressed. S2. Lattice distortion pretreatment: Immerse the billet in liquid nitrogen for 2-3 hours, then heat to room temperature; S3. Magnetic field-assisted sintering: 12-15 parts of FeCrAlY alloy powder are filled into the interlayer voids of the billet; Under a vertical magnetic field of 1–1.2T, the temperature is increased to 1450–1480℃ at a rate of 10–12℃ / min, and then hot-pressed and sintered at 48–50MPa for 1–2 hours. S4. Post-stress relief treatment: cryogenically cool to -85 to -80℃ and hold for 1 to 2 hours, followed by pulsed current aging.
2. The method for preparing a high-strength and high-toughness cemented carbide with a biomimetic layered structure according to claim 1, wherein in step S1, the plasma-modified CNT-BN hybrid is prepared by the following steps: Multi-walled CNTs and hexagonal BN nanosheets were placed in a plasma reaction chamber and an Ar / N2 mixed gas was introduced. The volume ratio of Ar to N2 was 4:1 to 4.5:
1. The mixture was treated for 30 to 40 minutes at a radio frequency power of 500 to 550 W and a gas pressure of 8 to 10 Pa, so that the BN nanosheets grew in situ on the CNT surface.
3. The method for preparing high-strength and high-toughness cemented carbide with a biomimetic layered structure according to claim 2, characterized in that, In step S1, the preparation of WC / BN slurry includes: Mix 25-30 parts of organic carrier with 0.4-0.6 parts of dispersant and stir until homogeneous to obtain liquid matrix one; Add 65-70 parts of WC powder, 0.3-0.5 parts of Y2O3 powder, 0.05-0.1 parts of plasma-modified CNT-BN hybrid and 1.5-2.5 parts of BN nanosheets to the liquid matrix and mix evenly. The preparation of TiC / BN slurry includes: Mix 15-18 parts of organic carrier with 0.1-0.2 parts of dispersant and stir until homogeneous to obtain liquid matrix II; Add 9-10 parts of TiC powder and 3.5-5.5 parts of BN nanosheets to the liquid matrix II and mix thoroughly. The organic carrier is a 6-8 wt% polyvinyl butyral / ethanol solution, and the dispersant is herring oil.
4. The method for preparing high-strength and high-toughness cemented carbide with a biomimetic layered structure according to claim 3, characterized in that, In step S3, the FeCrAlY alloy composition is Fe 70-73wt%, Cr 18-22wt%, Al 5-8wt%, and Y 0.5-1wt%.
5. In the method for preparing high-strength and high-toughness cemented carbide with biomimetic layered structure according to claim 4, in step S3, the temperature is increased at a rate of 0.5℃ / min in the range of 1000-1200℃ during the hot pressing sintering process.
6. In the method for preparing high-strength and high-toughness cemented carbide with biomimetic layered structure according to claim 5, in step S4, the cryogenic treatment is performed by liquid nitrogen spraying at a rate of 5 to 5.5 L / min, and the surface temperature gradient of the billet is ≤50℃ / cm.
7. The method for preparing high-strength and high-toughness cemented carbide with a biomimetic layered structure according to claim 6, characterized in that, In step S4, the pulse current aging parameters are: peak temperature 600-620℃, frequency 50-55Hz, and cumulative time 30-40min.
8. A cutting tool, characterized in that, The cutting tip is made of an alloy prepared by the biomimetic stacked high-strength and tough cemented carbide preparation method according to any one of claims 1 to 7, wherein the biomimetic stacking direction of the cutting tip forms a 45° angle with the cutting force direction.
Citation Information
Patent Citations
Nano-composite coating hard alloy cutter for intermetallic compound / high-temperature alloy machining and preparation method of nano-composite coating hard alloy cutter
CN119346874A
Cutting tool and machining method for titanium alloy material
CN119588936A